Rancang Bangun Sistem Informasi Pembuatan Surat Undangan Bintang Tamu Pada TVRI Sumatera Utara - Rifani Khairani Pohan (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
The information system for making invitation letters for guest stars at TVRI North Sumatra is designed to increase efficiency in managing invitations and guest information. This research aims to identify various challenges faced during the implementation of practical work at TVRI, such as administrative problems and employee delays. Through the use of web-based technology, this application is expected to provide practical and relevant solutions, facilitating the process of making invitations, managing guest data, and confirming attendance. The system development method used includes requirements analysis, user interface design, and implementation using HTML, CSS, JavaScript, and PHP for database management. It is hoped that the results of this research will be able to make a significant contribution to the efficiency of TVRI's internal processes, as well as creating valuable practical experience in the field of information technology.